Cultura e memória do povo de Arrojado - Lavras da Mangabeira, Ceará - Bezerra, Herbenio de Souza (2024)
This study was based on the following research question: What are the elements that are part of of the culture and collective memory of the people of Arrojado - Lavras da Mangabeira, Ceará? In order to answer it, the main objective was to reveal the elements that are part of the the culture and memory of the people of Arrojado and that help to understand their identity. To achieve this aim, the research was broken down into the following specific objectives: a) to get to know the current daily life of the residents of Arrojado; b) to investigate the identity aspects common to the inhabitants of the district; c) to record part of the collective memory of the local people, by identifying their individual memories. The theoretical framework is based on the ideas that form the concepts of culture and memory. For the former, it traced a brief history of the evolution of the concept of culture in the social sciences, showing its symbolic forms and the construction of identity. For the second idea, it used three different conceptions of memory: as the capacity to remember, as materialized knowledge and from a social perspective. The methodological was based on ethnography, a way of conducting research that is characterized as exploratory, qualitative and descriptive. The data was collected through semi-structured interviews with women over 60 who live in Arrojado. In addition to their accounts, observations were made in the field. Bardin's content analysis technique was used to analyze the data, which resulted in the establishment of three conceptual categories: Spaces, People and Objects. It concluded that, in the midst of the tranquil daily life of Arrojado, its residents make use of various tactics in the face of social and cultural impositions. The inhabitants of the district update their traditions in the midst of the reality of the contemporary world. It points to the need to develop cultural preservation and memory initiatives, preventing its elements from being lost with the passage of time.